Special Issue on new therapeutic approaches to Parkinson disease. (1st May 2022) - Fox, S.H.; Brotchie, J.M.
Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder. Age is the biggest risk factor, with the prevalence rising from 1% in 45–54 year age group to 2–4% in 85 year or older. Population increases have led some to predict that we are facing a 'PD Pandemic' with the prevalence doubling in the next two decades. There is thus an urgent need for effective therapies to reduce disease burden. In this Special Issue of Neuropharmacology invited authors have reviewed current and emerging targets for pharmacological therapy for PD covering the areas of disease modification, i.e. addressing the underlying disease processes, through to symptomatic therapies, whether for motor or non-motor symptoms of the disease. The articles are from leaders in the field and represent preclinical and clinical stages of therapeutic development. The Special Issue highlights that there is ongoing significant activity across all these potential indications and a vast array of targets have been identified and validated to different extents. PD is, and will remain for the foreseeable future, for the neuropharmacologist a significant area of research, in both the preclinical and clinical space.